Studi metode invigorasi pada viabilitas dua lot benih kedelai yang telah disimpan selama sembilan bulan - . Nurmauli; Yayuk Nurmiaty (Institut Pertanian Bogor, 2010)
Invigoration is one method to solve the problem of overdue seeds. Seeds are treated before planting to stimulate the metabolism activities inside the seeds so that seeds are equipped to emerge. Invigoration method could be applied using osmo-conditioning (Polyethylene Glycol (PEG-6000) solution) or matriconditioning, and hydrate-dehydrate treatment. Invigoration started when seeds imbibe in a solution with low water potential until seed water content could be reserved after its equilibrium.This study was conducted in Seed technology and breeding laboratory, Faculty of Agriculture, Lampung University in June 2009. Seeds testing with osmo-conditioning including: (1) hydrate-dehydrate treatment with aqua bides and (2) immersed into Polyethylene Glycol (PEG) with 10 and 20% concentration. Observations were including: seeds emerge ability, sprout identical growth, dry mass of normal seeds, and electrical conductance. All data were analyzed, described and presented with statistical methods and with histogram. The results showed that: (1) Anjosmoro soybean seeds status which were overdue during storage were moderate stability which were showed by emerge viability observation (<70%) and (2) viability restoration and anjosmoro soybean seeds vigor which were overdue during storage using invigoration method tended to be the highest which were showed by observing seeds emerged ability, sprout identical growth, and sprout dry mass together with low electrical conductance.